Health system capacity and readiness for delivery of integrated non-communicable disease services in primary health care: A qualitative analysis of the Ethiopian experience. - Azeb Gebresilassie Tesema; Seye Abimbola; Afework Mulugeta; Whenayon S Ajisegiri; Padmanesan Narasimhan; Rohina Joshi; David Peiris (Public Library of Science (PLoS), 2021)
Background Non-communicable diseases (NCDs) now account for about 71% and 32% of all the deaths globally and in Ethiopia. Primary health care (PHC) is a vital instrument to address the ever-increasing burden of NCDs and is the best strategy for delivering integrated and equitable NCD care. We explored the capacity and readiness of Ethiopia's PHC system to deliver integrated, people-centred NCD services. Methods A qualitative study was conducted in two regions and Federal Ministry of Health, Addis Ababa, Ethiopia. We carried out twenty-two key informant interviews with national and regional policymakers, officials from a partner organisation, woreda/district health office managers and coordinators, and PHC workers. Data were coded and thematically analysed using the World Health Organization (WHO) Operational Framework for PHC. Results Although the rising NCD burden is well recognised in Ethiopia, and the country has NCD-specific strategies and some interventions in place, we identified critical gaps in several levers of the WHO Operational Framework. Many compared the under-investment in NCDs contrasted with Ethiopia's successful PHC models established for maternal and child health and communicable disease programs. Insufficient political commitment and leadership required to integrate NCD services at the PHC level and weaknesses in governance structures, inter-sectoral coordination, and funding for NCDs were identified as significant barriers to strengthening PHC capacity to address NCDs. Among the operational-focussed levers, fragmented information management systems and inadequate equipment and medicines were identified as critical bottlenecks. The PHC workforce was also considered insufficiently skilled and supported to provide NCD services in PHC facilities. Conclusion Strengthening NCD prevention and control through PHC in Ethiopia requires greater political commitment and investment at all health system levels. Prior success strategies with other PHC programs could be adapted and applied to NCD policies and practice, giving due consideration for the unique nature of the NCD program.